Anomalous signals before 2011 Tohoku-oki Mw9.1 earthquake, detected by superconducting gravimeters and broadband seisimometers - Gu Xiang; Jiang Tianxing; Zhang Wenqiang; Huang Weiliang; Chang Zhiqiang; Shen Wenbin (Geodesy and Geodynamics, 2014)
The 2011 Tohoku-oki earthquake, occurred on 11 March, 2011, is a great earthquake with a seismic magnitude Mw9.1, before which an Mw7.5 earthquake occurred. Focusing on this great earthquake event, we applied Hilber-Huang transform (HHT) analysis method to the one-second interval records at seven superconducting gravimeter (SG) stations and seven broadband seismic (BS) stations to carry out spectrum analysis and compute the energy-frequency-time distribution. Tidal effects are removed from SG data by T-soft software before the data series are transformed by HHT method. Based on HHT spectra and the marginal spectra from the records at selected seven SG stations and seven BS stations we found anomalous signals in terms of energy. The dominant frequencies of the anomalous signals are respectively about 0.13 Hz in SG records and 0.2 Hz in seismic data, and the anomalous signals occurred one week or two to three days prior to the event. Taking into account that in this period no typhoon event occurred, we may conclude that these anomalous signals might be related to the great earthquake event.